A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae) - Sabella, Giorgio; Viglianisi, Fabio Massimo; Bekchiev, Rostislav (Zootaxa, 2019)
Pselaphogenius chloe sp. n. belonging to the fiorii species group is described. The distribution of the 12 species belonging to this group is detailed and an identification key is provided. The hypothesis that the current distribution and the differentiation of the species of the Pselaphogenius of the fiorii group have been determined by the Pleistocenic glaciations is discussed.